Diversity and Inclusion in the Global Workplace Aligning Initiatives with Strategic Business Goals (Springer International Publishing, 2018)
This edited collection offers a nontraditional approach to diversity management, going beyond gender, race, and ethnicity. Examining ageism, disability, and spirituality, the book provides a discussion of different D&I applications and introduces a framework consisting of a diagnostic phase, gap analysis, and an action plan, which can be modified to attend to specific needs of organizations. Researchers and practitioners will learn a viable way to address diversity in global organizations.